Pengaruh DPK, FDR dan NPF Terhadap Pembiayaan Murabahah Pada BPR Syariah Harta Insan Karimah Untuk Periode 2020-2022 - Cahya, Nilam; Wirman, Wirman (Jurnal Ilmiah Wahana Pendidikan, 2024)
This examination intends to find out and test whether there is an impact between the DPK, FDR and NPF factors on murabahah supporting at the Harta Insan Karimah Sharia Individuals' Funding Bank. This exploration utilizes quantitative techniques with auxiliary information got as Quarterly Monetary Reports on the authority BPR Syariah Harta Insan Karimah site. The information investigation strategy utilizes the old style supposition test, numerous relapse examination test and speculation testing utilizing the T test and F test. The exploration results show that to some extent the DPK, FDR and NPF factors meaningfully no affect Murabahah funding. This can be demonstrated that the DPK got an importance worth of 0.194 > 0.05. For the FDR variable, the importance esteem was 0.534 > 0.05. Then, at that point, the NPF variable got an importance worth of 0.490 > 0.05. In the interim, at the same time the factors DPK, FDR, and NPF impact Murabahah with an importance worth of 0.009 < 0.05